Design and validation of a self-powered device for wireless electronically controlled pneumatic brake and onboard monitoring in freight wagons. (1st July 2021) - Zuo, Jianyong; Dong, Liwei; Ding, Jingxian; Wang, Xueping; Diao, Pengfei; Yu, Jie
Highlights: A self-powered device is designed for utilizing freight car vertical motion. A vehicle-track coupled model is established for the excitation analysis. The theoretical maximum average power of this novel device is 50.26W. The output can meet the power demand of ECP brake and onboard monitoring. Abstract: Electronically controlled pneumatic (ECP) brake system achieves better brake consistency because of fast braking command transmission, but the practical application is limited by the lack of power transmission in standard railway freight wagons. This paper presents the excitations analysis, design, modelling and experimental validation of a novel self-powered device (SPD) utilizing vertical mechanical energy of freight car for onboard power supply. The device with ball crew, mechanical motion rectifier, gearbox and generator converts the bi-directional vertical translation between the car body and bogie into the unidirectional rotation of generator. The electromechanical coupled model of SPD is established to predict the performance versus different load conditions and train speeds. A peak voltage of 29.3 V and an average power of 50.26 W with 16 Ω external resistance are obtained when the full-loaded vehicle speed is 100 km/h, which indicates the potential of single device to power the wireless ECP brake system and sensor nodes simultaneously. The experiments are carried out and the results are in good agreement with the simulations. Moreover, the SPD adapts well to the broadband characteristics of railcars vertical vibration. The experimental results show that an average power of 4.6 W is achieved even in unfavorable condition. This onboard SPD as distributed power supply in unpowered freight car will realize the popularization of more smart devices and improve the overall performance of heavy-haul trains with long group.